Enhancing adolescent psychological well-being through habitual physical activity: exploring the mediating role of self-esteem - Abdul Malik, Mohd Azry; Razali, Aina Safiera; Zaiyad, Nurfadilah; Ismail, Nor Azima; Ghazali, Jasrul Nizam; Sahroni, Mohamad Norzamani (Faculty of Sports Science and Recreation, 2024)
Physical activity is an essential contributor to adolescents' psychological well-being. This research aims to explore the impact of habitual physical activity on the self-confidence and self-esteem of teenagers. Additionally, the study investigates the mediating role of self-esteem in the connection between habitual physical activity and adolescent self-confidence. The sample comprises 286 teenagers from a prominent higher education campus in Kelantan, and data collection is carried out through self-administered questionnaires. Ordinary least squares estimation is used for data analysis. The findings reveal a significant positive effect of habitual physical activity on confidence and selfesteem. Moreover, self-esteem is identified as a significant mediator in the relationship between habitual physical activity and self-confidence. Interestingly, the study does not observe a significant difference in self-confidence levels between genders. The anticipated outcome of this study is to offer valuable insights for the government, higher education administrators, and policymakers to advocate for the active participation of adolescents in physical activities, fostering positive psychological health among them.